Biologic profile evaluation of mesenchymal stem cells in co-culture with K562 cells - Farshchi, Niloofar; Azandeh, Saeed; Jalali, Mohammad; Saki, Najmaldin (Clinical cancer investigation journal, 2020)
Background: Mesenchymal stem cells (MSCs) are among the most essential components of bone marrow (BM) microenvironment. Any infiltration of malignant cells or malignancy of BM cells could affect the fate of other cells in the BM microenvironment. Several studies have assessed the function and phenotype of BM-derived MSCs in leukemia patients, which have presented different results. Our goal in this research was to examine the cytogenetic and flow cytometric profiles as well as the growth of human umbilical cord MSCs (hUC-MSC) after co-culture with a chronic myeloid leukemia cell line, namely K562. Subjects and Methods: MSCs were isolated as a primary culture from hUC, co-cultured with K562 cells and examined in two groups of control (MSCs) and test (hUC-MSCs + K562 cells). Using karyotypic and flow cytometric techniques, cytogenetic and surface markers, as well as growth patterns of MSCs, were investigated in the two groups by plotting the growth curves. Results: MSCs cultured in the test group (together with K562 cells) were morphologically similar to those in the control medium. Cytogenetic analysis of MSCs in the test group indicated no chromosomal abnormalities; however, there were significant differences in the expressions of surface markers as well as in MSCs growth curves between control and test groups. Discussion/Conclusion: K562 cells do not have the ability to induce cytogenetic changes in MSCs, but they are capable of altering the expressions of surface markers as well as growth rates of MSCs.